Policy and Behavioral Gaps in Achieving Indonesia’s Renewable Energy Mix Target - Yoesgiantoro, Donny; Yusgiantoro, Filda Citra; Rahmawati, Rahmawati (International Journal of Energy Economics and Policy, 2026)
The target of achieving 23% renewable energy in the energy mix by 2025 remains distant, as the actual figure in 2024 stands at only 13.1%. This study attempts to review the issue through the lens of the extended Theory of Planned Behaviour (TPB), aiming to understand the core reasons behind the failure to meet this target from the perspective of public behaviour. The focus is on assessing the impact of policy support on public behaviour regarding the adoption of new and renewable energy (NRE). The research employs a quantitative approach, involving 402 respondents from across Indonesia. Data were collected via an online survey and processed using structural equation modelling based on analysis of moment structures (SEM-AMOS). Empirical results demonstrate that all the hypotheses tested were supported. It was shown that policy support has a direct effect on attitude, subjective norms, perceived behavioural control (PBC), and the intention to use NRE. Notably, the hypothesis positing that attitude, subjective norms, and PBC mediate the relationship between policy support and the intention to use NRE was also supported. Furthermore, the public’s evaluation of incentive policies designed to encourage community engagement with NRE received high scores, ranging from 7 to 8.3 on a 10-point scale. Overall, the findings reveal that the low level of NRE utilisation in the energy mix is attributable to limited public awareness of the policy, with 63% of the population unaware of its existence. Therefore, to achieve the target, the government must promptly develop an effective campaign strategy to raise public awareness and understanding of the NRE incentive policy over the long term. As a practical recommendation, the government should immediately implement such a campaign to enhance public knowledge and support for NRE incentives.